Malt extract as a raw material for modern coffee drinks - Ivanov, Yevhenii; Shutyuk, Vitaliy (My University, 2020)
The possibility of using malt extracts of cereals in the development of modern beverage technologies is considered in the work. It is shown that malt extracts are a promising raw material for coffee and functional drinks.
Keywords: солод; екстракт; напої; malt; extract; drinks; кафедра технології консервування